CASE STUDY OF HOST AND ENVIRONMENT FACTORS ON DHF INCIDENCE IN LIMA PULUH DISTRICT: Studi Kasus Faktor Host dan Lingkungan Terhadap Kejadian DBD di Kecamatan Lima Puluh - Tarianna Ginting; Putri Yunita Pane; Eka Lolita Eliyanti Pakpahan; Dameria Gultom; Sari Indriyani (Universitas Airlangga, 2023)
Background: In the last fifty years, dengue hemorrhagic fever (DHF) has increased 30 times in 100 endemic countries. As a tropical country, Indonesia is one of the endemic countries for DHF cases, which often cause